Ab-initio studies of adsorbate-surface interactions - Rêgo, Celso Ricardo Caldeira (2017)
This thesis supplies a contribution to the understanding of the interaction between carboncarbon surfaces, atoms with carbon-surfaces, and atoms with metallic surfaces. It is well established that the surface-surface and atom-surface interactions are interesting, important and challenging for reasons that vary from industrial interest up to the academic necessity of understanding it deeply. Currently, there are many measurements and simulations for the geometric and electronic properties of Graphite, these differ by more than 40%. This implies that our understanding of the nature of this material is quite poor. The interaction between small transition-metals clusters with a Graphene sheet is another example where our knowledge is very limited. There are many theoretical studies in the literature that describe the interaction between these clusters with a Graphene sheet, but they agree and disagree on many points, which calls for systematic study of this issue. In this thesis we will focus our efforts on studying the surface-surface and atom/clusters-surface interactions. This thesis is split into three projects. The first aims to contribute to the understanding of the interlayer interactions of the bulk Graphite. In the second, we intend to shed some light on comprehending the interaction of an adatom with a Graphene sheet. Both of these projects, are studied within DFT framework with the inclusion of the van der Waals (vdW) corrections. In the Graphite project, we found that the electronic and geometric properties depend on the vdW correction employed in the calculation. In the adatom supported on Graphene project, we combined a modified Anderson-Newns model to describe the coupling between the adatom with Graphene. In addition, we found the existence of competition between quantum and classical forces, which determine the type of site in which the adatom prefers to adsorb. The last project is a dynamical study of an atom that impinges upon a metallic surface. In this project, we focus on the calculation of the sticking coefficient, a measure of the amount of nuclear density attached to the metal surface after collision. At this time the project is not one 100% ready, but our preliminary results indicates that, a small part of the nuclear density stays stuck on the metal.